Digital Society and the Transformation of Community-Based Dispute Resolution in Indonesia - Ardhitama Sucahyanto (JUSTISIA GLOBAL EDUKASI, 2026)
The expansion of digital technology has significantly transformed social interactions, communication patterns, and dispute resolution processes within Indonesian society. Traditional community-based dispute resolution mechanisms, which have long served as accessible and culturally legitimate means of conflict management, are increasingly influenced by digital platforms and online communication networks. This study investigates the transformation of community-based dispute resolution in Indonesia within the context of an emerging digital society. Using a sociolegal research framework, the study explores how digital technologies affect the legitimacy, effectiveness, and accessibility of local dispute resolution practices. The findings demonstrate that digital communication tools facilitate faster information exchange, broader public participation, and increased transparency in dispute management processes. At the same time, the digitalization of social relations introduces new challenges, including misinformation, online harassment, privacy concerns, and the emergence of digitally mediated conflicts. The study further reveals that community leaders and local institutions increasingly utilize digital platforms to support mediation and consensus-building efforts while maintaining traditional values and social norms. Effective adaptation requires balancing technological innovation with cultural legitimacy and procedural fairness. The research argues that the evolution of community-based dispute resolution reflects broader changes in legal consciousness and social governance within Indonesia’s digital transformation. The study concludes that sociolegal frameworks must adapt to the realities of digital society while preserving the inclusive and participatory character of local dispute resolution mechanisms. These findings contribute to contemporary debates on law, technology, and community governance in developing societies.